Pre-treatment serum apolipoprotein E: a promising prognostic indicator for nasopharyngeal carcinoma - Xian-Ming He; Si-Cong Jiang; Qi-Wei Luo; Jian-Wu Ding; Rong-Huan Hu; Jia-Li Hu; Meng-Meng Liu; Lei Tao; Jian-Ze Zhang; Jia-Yin Wu; Su Deng; Lei Zeng (European Journal of Medical Research)
Abstract Background and purpose This preliminary study explores the prognostic value of pretreatment peripheral serum apolipoprotein E (ApoE) in patients with non-metastatic nasopharyngeal carcinoma (NPC). Materials and methods A retrospective collection of pretreatment indicators was conducted for 352 nasopharyngeal carcinoma patients between January 2016 and December 2020. Receiver operating characteristic curve analysis, univariate and multivariate Cox proportional hazards analysis were all utilized to assess the correlation between blood ApoE and overall survival (OS), progression-free survival (PFS), distant metastasis-free survival (DMFS) and local recurrence-free survival (LRFS). Results A higher baseline serum ApoE level (> 71.5 mg/L) was markedly associated with poorer OS (HR = 2.255, 95% CI 1.232–4.125, P = 0.008) and remained an independent prognostic factor in multivariate Cox regression analysis. Additionally, body mass index (BMI), body surface area (BSA), Epstein-Barr virus (EBV)DNA load, and high-density lipoprotein cholesterol (HDL-C) were also identified as independent predictors of nasopharyngeal carcinoma prognosis. Conclusion An elevated pretreatment serum ApoE level is indicative of a poorer prognosis for nasopharyngeal carcinoma patients and is independent of other known prognostic factors. These findings highlight the value of ApoE as a potential biomarker for risk stratification and personalized treatment in nasopharyngeal carcinoma.